Ternary molten salt as a phase change material : A review - Li, Li; Muhamad, Mat Noor; Kadirgama, Kumaran; Samylingam, Lingenthiran; Harikrishnan, Santhanam (Semarak Ilmu Publishing, 2024)
Phase change materials have gained much attention due to their excellent properties.This research paper delves into the utilization of ternary molten salt as a thermal storage medium for Thermal Energy Storage (TES) within the context of Concentrated Solar Power (CSP) systems. Meanwhile, different types and compositions of molten salts are discussed in detail in this paper. Molten salts are used extensively as heat transfer media and in the production of solar power because of their special qualities and affordable cost. Nitrates are less expensive, less corrosive, and do not break down below 500 °C when compared to other molten salts. For this reason, the primary heat storage component of solar power generation is mixed molten nitrate salts.